2021
DOI: 10.1021/acs.iecr.1c01376
|View full text |Cite
|
Sign up to set email alerts
|

Porous Polyurea Supported Pd Catalyst: Easy Preparation, Full Characterization, and High Activity and Reusability in Reduction of Hexavalent Chromium in Aqueous System

Abstract: Developing efficient supports for transition-metal nanoparticles (M-NPs) to prevent their agglomeration and to facilitate their handling and recycled use has been a constant objective. Herein, porous polyurea (PPU) is prepared by simple precipitation polymerization of toluene diisocyanate through its reaction with water in water–acetone, followed by Pd­(OAc)2 immobilization on a PPU surface to get Pd­(OAc)2@PPU and by Pd­(OAc)2 reduction to get a hybrid composite Pd@PPU with Pd-NPs on a PPU surface. Multiple c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Photocatalysis is one of the most popular techniques because of the simplicity of the hardware design, high efficiency, and low cost of the process [10,11]. Various types of nanoscale materials have previously been studied as effective catalysts for the removal of chromium(VI) ions [8,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysis is one of the most popular techniques because of the simplicity of the hardware design, high efficiency, and low cost of the process [10,11]. Various types of nanoscale materials have previously been studied as effective catalysts for the removal of chromium(VI) ions [8,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Cr 6+ is highly toxic and has been classified as a human respiratory carcinogen. 30,44,45 Fluorescent sensors are extensively used as a powerful means due to their simplicity, rapidity, and excellent sensitivity for Cr 6+ detection. 45−48 In order to explore the possibility to use PUSi3 microspheres as a sensor to detect Cr 6+ in water, the emission of PUSi3 6A, which revealed that, among the 16 ions tested, the emission was distinctly attenuated only by Cr 6+ and Fe 3+ , and practically no effect or a slight decrease in emission intensity was detected for the rest of the ions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Cr 6+ is highly toxic and has been classified as a human respiratory carcinogen. ,, Fluorescent sensors are extensively used as a powerful means due to their simplicity, rapidity, and excellent sensitivity for Cr 6+ detection. In order to explore the possibility to use PUSi3 microspheres as a sensor to detect Cr 6+ in water, the emission of PUSi3 dispersion (10.0 mg/mL) was measured in the presence of Cr 6+ (200 μmol/L). It was found that the emission intensity sharply declined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are difficult to decompose using conventional treatment procedures. Adsorption and flocculation, which are common dye effluent treatment techniques, are inefficient because they produce solid residue, which causes other environmental issues and needs further treatment [17][18][19]. Transition metal-related oxidative methods have demonstrated increased removal efficiency for the degradation of carcinogenic pollutants into lower molecular weight and reduced toxicity [20][21].…”
Section: Introductionmentioning
confidence: 99%